Main ion and impurity edge profile evolution across the L- to H-mode transition on DIII-D. (15th August 2018) - Haskey, S R; Grierson, B A; Chrystal, C; Ashourvan, A; Burrell, K H; Groebner, R J; Belli, E A; Stagner, L; Battaglia, D J; Stoltzfus-Dueck, T; Bortolon, A
Abstract: Detailed measurements of the main ion ( D + ) and impurity ion ( C 6 + ) evolution during the development of the H-mode pedestal across an L–H transition show significant differences in toroidal rotation, density, and temperature profiles in the pedestal region on DIII-D. While both species experience a slow toroidal spin up at constant input neutral beam injected torque, the C 6 +  toroidal rotation develops a non monotonic notch feature and lower toroidal rotation near the plasma edge immediately following the L–H transition. This feature is not present in the main ion rotation that instead, depending on plasma parameters, can show a flat or peaked rotation near the separatrix. The D +  and C 6 +  temperature profiles show a similar evolution; however, the D + temperature is lower than the C 6 +  temperature at the separatrix in both L and H-mode which may be due to cooling of D +  via charge exchange with cold edge deuterium neutrals. Local neoclassical predictions of the main ion toroidal rotation based on the impurity properties show good agreement with direct measurements at the pedestal top for a lower power, higher collisionality case but can diverge significantly in the steep gradient region for the two shots studied here. These observations highlight the importance of directly measuring the properties of the main ion species at the plasma edge.